Contribution of snow and glacier melt to discharge for highly glacierised catchments in Norway - M. Engelhardt; T. V. Schuler; L. M. Andreassen (Hydrology and Earth System Sciences, 2014)
Glacierised catchments show a discharge regime that is strongly influenced by snow and glacier meltwaters. In this study, we modelled the mass balance and discharge rates for three highly glacierised catchments (>50% glacier cover) in western Norway over the period 1961–2012. The spatial pattern of the catchments follows a gradient in climate continentality from west to east. The model input were gridded temperature and precipitation values from seNorge ( http://senorge.no ) which are available at daily resolution. The model accounted for accumulation of snow, transformation of snow to firn and ice, evaporation and melt. Calibration and validation were performed for each catchment based on measurements of seasonal glacier mass balances and daily discharge rates, as additional validation data served daily melt rates from sonic rangers located in the ablation zones of two of the glaciers. The discharge sources snowmelt, glacier melt and rain were analysed with respect to spatial variations and temporal evolution. Model simulations reveal an increase in the relative contribution from glacier melt to total discharge for the three catchments from less than 10% in the early 1990s to 15–30% in the late 2000s. The decline in precipitation by 10–20% in the same period was therefore overcompensated, resulting in an increase in annual discharge by 5–20%. Annual discharge sums and annual glacier melt are most strongly correlated with annual and winter precipitation at the most maritime glacier and, with increased climate continentality, variations in both glacier melt contribution and annual discharge are becoming more strongly correlated with variations in summer temperatures. Therefore, glaciers in more continental climates are especially vulnerable to decrease in both annual and summer discharge with continued rise in summer temperatures and subsequent decrease in glacier extent. This may lead to significant changes to the discharge regime, with increase during spring but decline later in the year, especially for ...